2005
DOI: 10.1002/elps.200410433
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle‐filled capillary electrophoresis for the separation of long DNA molecules in the presence of hydrodynamic and electrokinetic forces

Abstract: We report the analysis of long DNA molecules by nanoparticle-filled capillary electrophoresis (NFCE) under the influences of hydrodynamic and electrokinetic forces. The gold nanoparticle (GNP)/polymer composites (GNPPs) prepared from GNPs and poly(ethylene oxide) were filled in a capillary to act as separation matrices for DNA separation. The separations of lambda-DNA (0.12-23.1 kbp) and high-molecular-weight DNA markers (8.27-48.5 kbp) by NFCE, under an electric field of -140 V/cm and a hydrodynamic flow velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 42 publications
0
44
0
3
Order By: Relevance
“…Separation of naphthalene, biphenyl and thiourea [29] Baseline separation of dopamine and epinephrine [30] Neurotransmitters (dopamine and epinephrine) and environmental pollutants [31] Separation of thiourea, naphthalene, biphenyl and of the selected polycylic aromatic hydrocarbons [32] Immobilized dodecane thiol gold nanoparticles [33] Reversed-phase test mixture of three steroid drugs [34] Gold-based nanoparticles to manipulate selectivity [35] PEO solution containing gold nanoparticles to analysize DNA fragments in CZE [36,37,39] DNA separation in MCE using low-viscosity PEO (gold nanoparticle) solution [40,41] Silica nanoparticles…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Separation of naphthalene, biphenyl and thiourea [29] Baseline separation of dopamine and epinephrine [30] Neurotransmitters (dopamine and epinephrine) and environmental pollutants [31] Separation of thiourea, naphthalene, biphenyl and of the selected polycylic aromatic hydrocarbons [32] Immobilized dodecane thiol gold nanoparticles [33] Reversed-phase test mixture of three steroid drugs [34] Gold-based nanoparticles to manipulate selectivity [35] PEO solution containing gold nanoparticles to analysize DNA fragments in CZE [36,37,39] DNA separation in MCE using low-viscosity PEO (gold nanoparticle) solution [40,41] Silica nanoparticles…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…This additional partitioning effect enables the separation not only of charged analytes but also of neutral species, provided that the NPs possess residual charges. Additionally, NPs are effective for the separation of hydrophobic compounds that are not easily resolved by a micellar pseudostationary phase in MEKC [24]. CGE is an adaptation of traditional gel electrophoresis for the analysis of proteins, DNA, and RNA.…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…The use of NPs as the pseudostationary phase was introduced by Wallingford and Ewing in 1989 [21]. Since then, many papers and reviews have reported the combination of MEKC and NPs [22][23][24]. The addition of NPs to the running buffer improves the separation by providing additional sites for the interaction with analytes.…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…Since then, the major part of work has focused on analysis of low-molecular-weight compounds [15][16][17]. However, there are some examples of separation of high molecular weight compounds, such as DNA [18][19][20][21] and proteins [22][23][24][25][26][27][28]. Conventional DNA separations in CE based on physical polymer gels are limited by the high viscosity of the polymer solution, which makes replenishment cumbersome.…”
Section: Introductionmentioning
confidence: 99%